The Growth of Red Spinach (Amaranthus tricolor L.) After Application of Bean Sprouts Extract [Vigna radiata (L.) R. Wilczek] on Murashige and Skoog Medium In Vitro - Herlanda, Kishy Dhea; Nurcahyani, Endang; Mahfut, Mahfut; Handayani, Tundjung Tripeni (Bioeksperimen: Jurnal Penelitian Biologi, 2023)
Red spinach (Amaranthus tricolor L.) is a commercially valuable vegetable known for its high nutritional content and immune-boosting properties, making it popular among the Indonesian population. However, red spinach cultivation in Indonesia is still relatively low and inconsistent, necessitating efforts to enhance its cultivation. One potential approach is through in vitro culture techniques. This study aimed to investigate the impact of applying mung bean sprout [Vigna radiata (L.) R. Wilczek] extract on Murashige and Skoog medium, focusing on identifying the most effective concentration for in vitro growth of red spinach explants. The experimental design employed a Completely Randomized Design (CRD) with five concentration levels: 0%, 5%, 10%, 15%, and 20%. Each concentration was replicated five times, with each replication consisting of five red spinach seeds in individual culture bottles. Data analysis involved Levene's test, one-way ANOVA, and Tukey's Honestly Significant Difference (HSD) test at a significance level of 5%. The findings revealed that the application of mung bean sprout extract significantly influenced the height of plantlets, leaf count, root length, fresh weight, and soluble carbohydrate content of red spinach. The most effective concentration for promoting red spinach explant growth was determined to be 5%.